Possible Territories and Real Utopias. Contributions to the Theories of Transformation: Territorial Intelligence and Territorial Justice. - Bozzano, Horacio; Universidad Nacional De La Plata (Universidad Católica de Pereira, 2017)
The aim of this reflective article is to summarize the question about how the epistemological perspective of possible territories is contributing to the construction of Theories of the Transformation, during three decades. In Addition it has been included dialogues with the perspective of the real utopias in Wright (2015). The general hypothesis proposes a basic formula between People and Public Policies in order to co-construct another development: Possible Territories, Real Utopias or other concepts, but committing ourselves to the decision of transforming our world with the “legs of the table” of Latin American Territorial Intelligence: people, scientists, politicians and businessmen. The formula is theoretically organized around four hypotheses, which is applied using a method, Territorii, and supported on results of a wide amount of researches, carried out since 1984 and another research about development from 2014 called: the PIO Project UNLP-CONICET  “Integral Management of the Territory”. In this PIO, two Scientific Agenda have been operating by permanent work-tables have been producing concrete results in the subjects of “Informal Urbanizations” and “Territory-Industry-Environment”, cobuilding Power and Public Politics from People and Science with the participation of an own-language speaker actor: the Environment. Institutions and companies always participate in the dominant system´s framework in both facets: formality and informality.